2015
DOI: 10.1146/annurev-fluid-010814-014644
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Element Method Simulations for Complex Granular Flows

Abstract: This review article focuses on the modeling of complex granular flows employing the discrete element method (DEM) approach. The specific topic discussed is the application of DEM models for the study of the flow behavior of nonspherical, flexible, or cohesive particles, including particle breakage. The major sources of particle cohesion—liquid induced, electrostatics, van der Waals forces—and their implementation into DEM simulations are covered. These aspects of particle flow are of great importance in practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(118 citation statements)
references
References 125 publications
2
116
0
Order By: Relevance
“…The fact that moisture affects the mechanical response of granular materials suggests that such influence is not negligible. Powerful numerical tools for investigation of force networks and granular flows like the discrete element method have a great difficulty in assuming a distribution of the liquid, in particular, the liquid fraction forming bridges and their shape [46,172,194 ]. Since these factors are achievable in silica CCs, accurate simulations can be compared to opal mechanical performance, and, in turn, it may help refine the modeling of such aspects.…”
Section: P-h Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that moisture affects the mechanical response of granular materials suggests that such influence is not negligible. Powerful numerical tools for investigation of force networks and granular flows like the discrete element method have a great difficulty in assuming a distribution of the liquid, in particular, the liquid fraction forming bridges and their shape [46,172,194 ]. Since these factors are achievable in silica CCs, accurate simulations can be compared to opal mechanical performance, and, in turn, it may help refine the modeling of such aspects.…”
Section: P-h Curvesmentioning
confidence: 99%
“…Nevertheless, most work has focused on dry particulate systems (solid-gas) [37,42,43] and, more recently, colloidal and granular suspensions (solid-liquid) [44,45] because of the much simpler binary-phase scenario −even so, they are still poorly understood. The additional fluid phase in the unsaturated case strongly complicates the picture and justifies that, apart from the phenomenology, the physics of wet particulate systems have been little studied and remains largely unknown [35,46]. One reason is that, although liquid-particles behavior relies on nanoscale phenomena, most research has been limited to relatively large scales, from millimeter down to micrometer (as in wet granular media [24,35,36,39,47]).…”
Section: Introductionmentioning
confidence: 99%
“…However, for highly dense, quasi-static flows, where particle contacts are enduring and multiple, the soft-particle approach is, clearly, preferable. For a detailed review of these approaches, their corresponding algorithms, theoretical advances and applications we refer to recent reviews [21,51,[72][73][74] and the references therein.…”
Section: Discrete Element Methods (Dem)mentioning
confidence: 99%
“…Even though the majority of the references listed in these articles [21,51,[72][73][74] consider spherically shaped particles, particulate systems encountered in industry or nature are often made up of non-spherical and/or irregularly shaped particles. Studies have shown that particle geometry considerably affects the bulk dynamics of particulate mixtures.…”
Section: Discrete Element Methods (Dem)mentioning
confidence: 99%
See 1 more Smart Citation